PENGARUH PERLUASAN MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SAMPO DOVE DI SEMARANG - Ambarani Enka Putri; Apriatni Endang Prihartini; Andi Wijayanto (Universitas Diponegoro, 2013)
This study aimed to determine the effect of brand extension and product quality on purchase decisions of Dove shampoo in Semarang. Type of research used in this research is explanatory research with 100 respondents taken using accidental sampling techniques. The techinique of analysis used in this study was linear regression with SPSS for windows. The results showed that the brand extension have a significant effect (partial) on purchase decisions of Dove shampoo in Semarang of 17,5%. The variable quality of product also has a significant influence (partial) on purchase decisions Dove shampoo in Semarang of 31.3%. Variables brand extension and product quality simultaneously have significant influence to the purchase decision of 33.0%.